State’s Positive Obligations in the System of Doctrinal Approaches to the Interpretation and Application of the European Convention of Human Rights - Г. О. Христова (Теорія і практика правознавства, 2016)
Problem setting. According to the Law of Ukraine # 3477-IV «On implementation of judgments and application of the case-law of the European Court of Human Rights», 23.02.2006 (Art. 17) the courts of Ukraine apply the Convention for the Protection of Human Rights and Fundamental Freedoms and its Protocols (hereinafter – Convention, ECHR) and the case-law of the European Court of Human Right (hereinafter – the Court, ECtHR) as the source of law. By the Regulation of the Cabinet of Ministers of Ukraine # 431, 10.09.2014 the Government Commissioner on ECtHR matters has been authorized to co-ordinate «the implementation of the Court’s judgments, which are the interpretation of norms of Convention and its inalienable part, contain the norms of law and are subject to application in the way of implementation of international treaties». Such positions clearly show the aspiration of Ukraine to strengthen the role of European standards of human rights in national legal order. At the same time the case-law of the ECtHR covers not only the numerous legal standards related to concrete rights and freedoms, but also the doctrinal approaches to the interpretation and application of the ECHR which lay the foundation of the Court’s jurisprudence. There is lack of studies of such doctrinal approaches in Ukraine while the conditions of their application at the national level are generally unknown. Resent research and publications analyses. Such doctrinal approaches are well developed in the ECtHR case-law and are deeply explored by European scholars (i. e. R. Bernhardt, D. Gomien, D. Harris, G. Letsas, R. St. J. Macdonald, S. Maringele, F. Matscher, J. McBride, H. Petzold, M. de Salvia, L. Zwaak). Meanwhile a few Ukrainian researchers have paid attention to the problem of principles and methods of interpretation and application of the ECHR (L. Gouseynov, T. Doudash, V. Marmazov, P. Rabinovich, S. Fedic, L. Tsvigoun, S. Shevchouc and some others). The deep analysis of the doctrines, which are developed due to the Court’s case-law are absent in Ukrainian jurisprudence. Paper objective. Main objective of the article is to study the doctrine of state’s positive obligations to secure the conventional rights and the legal grounds of such obligations under the ECHR law in correlation with the other doctrinal approaches which are used by the ECtHR in the perspective of their implementation on the national level. Paper main body. As the basic concepts and principles (also known as the methods of interpretation and application of the Convention) official on-line resources of the Council of Europe indicate: dynamic purposive interpretation (the concept of “Convention as a Living Instrument”), the autonomous concepts, negative and positive obligations, subsidiarity, proportionality, just satisfaction, “margin of appreciation” of the state, equality of arms, horizontal application of rights and their hierarchy. Among them there are several doctrines (the doctrines of dynamic purposive interpretation, “margin of appreciation” of the state, autonomous concepts and the state’s positive obligations) which have been recognized and developed due to the Court’s jurisprudence. They accumulate the «unwritten law» of the Convention (as they are not mentioned in the text of ECHR) and aim to ensure the sequence and logic system of promotion and protection of human rights. They are closely interrelated and interdependent. These doctrines are more about the scope and character of the state’s obligations under the Convention, rather then the subject to direct application in court proceedings on domestic level. Meanwhile these doctrines provide the means of assessment of compliance of the national policies and legal practice in the field of fundamental rights and freedoms with the European standards. Conclusions of the research. Thus the principle doctrinal approaches to the interpretation and application of the human rights and fundamental freedoms ensure the conceptual and methodological unity of the law of the Convention. Due to the Court’s case-law these doctrines obtained official recognition, international authority, validity and credibility as well as the normative (regulative) features. So they shall be incorporated to the national legal order. For that they shall be well-known to all kinds of the state agents (legislative body, state administration and law-enforcement bodies and judiciary) who shall fulfill their duties with respect to the doctrinal standards. Key words: human rights, state’s positive obligations, “margin of appreciation” of the state, purposive dynamic interpretation, case-law of the European Court of Human Rights.